PENGARUH LOYALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN MENGGUNAKAN JASA PENGIRIMAN BARANG PADA PT.JNE DI PAMEKASAN - Soedradjad, noer (Universitas Madura, 2017)
The banking industry is the most rapidly growing industry. Both in terms of business volume, mobilization of public funds and lending. With the increasingly intense competition among Banks; this situation forces the bank industry to be more creative and innovative in obtaining sources of funding. Due to the liberalization of these banks, the competition to attract funds from the community is increasing. All are competing to withdraw funds from the community and then channel them back to the communities who need them both productively and consumptively. Because for a Bank, funds collected from the public are the main supporting factors for managing optimally that can generate maximum profit. So in the business world perbankkan; in addition to the public's trust to raise funds; also how the virgin managed by perbankkan, can be created a service product that interesting to society lot. So the business excellence of a bank; if able to create financial services products favored by the public, from various segmentation of the target market